Gender- and height-related limits of muscle strength in world weightlifting champions - Ford, L. E.; Detterline, A. J.; Ho, K. K.; Cao, W. (Journal of Applied Physiology, 2000)
To assess factors that limit human muscle strength and growth, we examined the relationship between performance and body dimensions in the world weightlifting champions of 1993-1997. Weight lifted varied almost exactly with height squared (Ht2.16), suggesting that muscle mass scaled almost exactly with height cubed (Ht3.16) and that muscle cross-sectional area was closely correlated with body height, possibly because height and the numbers of muscle fibers in cross section are determined by a common factor during maturation. Further height limitations of muscle strength were shown by only one male champion 183 cm and no female champions 175 cm. The ratio of weight lifted to mean body cross-sectional area was approximately constant for body-weight classes 83 kg for men and 64 kg for women and decreased abruptly for higher weight classes. These findings suggest a nearly constant fraction of body mass devoted to muscle in lighter lifters and a lesser fraction in heavier lifters. Analysis also suggests that contractile tissue comprises ~30% less body mass in female champions.